Pulling Off Stable Economic System Adhering Carbon Emissions, Urban Development and Sustainable Development Values - Cen Cai; Ran Qiu; Yongqian Tu (Frontiers Media S.A., 2022)
In today's world, sustainability has become a major concern. The current study attempts to look into the impact of six sustainable development values on economic growth and emissions of carbon footprints: freedom, equality, solidarity, tolerance, respect for nature, and shared mobility. The moderating importance of urban development in regulating the relationship of economic growth and carbon footprints has also been investigated in this study. The structural equation modeling (SEM) analysis technique was utilized to confirm pathways and verify path modeling in this work. Overall, 302 responses were selected for data analysis, and data were collected using a self-administered questionnaire with a random sampling technique. The study found that two of the six sustainable development values (tolerance and solidarity) have a beneficial impact on a country's economic growth. However, freedom, equality, respect for nature, and shared mobility are not indicators of a country's economic progress. Similarly, economic expansion helps to mediate the relationship between tolerance, solidarity, and carbon emissions. Although urban growth did not play a moderating role, it has a positive impact on carbon emissions. The current study suggests various implications for long-term development to improve an economy's or country's economic performance. Furthermore, complete emphasis must be paid to sustainable development values, which are more closely linked to economic growth but also help cut carbon emissions. Future research should look into the current model in other countries.